1983
DOI: 10.1111/j.1365-2125.1983.tb01546.x
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of [3H]‐ouabain binding to human lymphocytes.

Abstract: sodium/potassium pump sites were 43154 + 8037 molecules/cell (n = 25) in lymphocytes and 75474 ± 6764 (n = 9) molecules/cell in mixtures of mononucleated cells.5 Direct determination of the [3H]-ouabain binding capacity of lymphocytes can be performed with acceptable accuracy and precision using 30 ml whole blood. Provided high cell purity, this method may be useful, when studying sodium/potassium pump function in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In lymphocytes glycoside binding has been shown to be saturable, confined to a single site of high affinity, temperature-sensitive, slow to reach equilibrium, slow to reverse, and competitively inhibited by potassium (Quastel & Kaplan, 1975;Pedersen & Klitgaard, 1983). Our work has confirmed these qualitative observations in intact mononuclear leucocytes (the majority of which were lymphocytes), and has demonstrated the same properties in intact polymorphonuclear leucocytes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In lymphocytes glycoside binding has been shown to be saturable, confined to a single site of high affinity, temperature-sensitive, slow to reach equilibrium, slow to reverse, and competitively inhibited by potassium (Quastel & Kaplan, 1975;Pedersen & Klitgaard, 1983). Our work has confirmed these qualitative observations in intact mononuclear leucocytes (the majority of which were lymphocytes), and has demonstrated the same properties in intact polymorphonuclear leucocytes.…”
Section: Discussionsupporting
confidence: 77%
“…The equilibrium dissociation constants calculated from our data are similar to those found by Erdmann & Hasse (1975) in human erythrocytes (2.8 x 10-9 mol/l) and cardiac membranes (2.8 x 10-9 mol/l). Although other workers have reported values ranging from 2.9 to 7.8 x 10-9 mol/l for human erythrocytes we believe that these figures are based on experiments in which binding was not at equilibrium, and that a value of about 1 to 2 x 10-9 mol/l is a more accurate assessment of the true KD of glycoside binding to the membranes of intact erythrocytes (see Ford et al, 1979 (Baker & Willis, 1972 (Wiley et al, 1979;Pedersen & Klitgaard, 1983 ouabain binding characteristics in these, and other, cells is the very slow rate of both association and dissociation. The potential problems of studying a slowly equilibrating ligand-receptor interaction have been discussed by Aranyi (1979Aranyi ( , 1980 (Aranyi, 1979).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The observed rates of pump inhibition reflect a low rate of association of ouabain with pump. Ligand-binding studies with tritiated ouabain have previously demonstrated low rates of association of ouabain with the Na+-K+ pump of human leucocytes at ouabain concentrations of 108mol 1-1 or less (Boon et al, 1984;Pedersen & Klitgaard, 1983). Except for the extreme concentrations of ouabain studied, which caused either no inhibition (10'0°mol 1-l) or an immediately obtained maximal inhibition (105mol L-), a steady-state level of pump inhibition was observed after about 2.5 h incubation of both MNL and PMNL with ouabain.…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain binding to the pump has been used to estimate the number of pump units, because of the 1:1 molar stoichiometry (Glynn & Karlish, 1975), and the binding characteristics of ouabain to various types of leucocytes have been described (Boon et al, 1984;Pedersen & Klitgaard, 1983). However, binding characteristics have not been compared with measurements of the effect of ouabain on pump activity.…”
Section: Introductionmentioning
confidence: 99%